Hamlet - Shakespeare, William, 1564-1616.; Crowther, John (John C.) (New York : SparkNotes, 2003)
Presents the original text of Shakespeare's play side by side with a modern version, with marginal notes and explanations and full descriptions of each character.
Keywords: Hamlet -- (Legendary character) -- Drama; Shakespeare, William, -- 1564-1616.; Murder victims' families -- Drama; Fathers -- Death -- Drama; Princes -- Drama; Revenge -- Drama; Plays; English literature -- History and criticism; Denmark -- Drama; Tragedies